ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIKA KELAS X DITINJAU DARI GAYA BELAJAR SISWA - Dinda Tantri Nureika Lailani; Indra Martha Rusmana (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to analyze and improve students' mathematical critical thinking skills in terms of learning styles in class X MIPA 1 students at SMAN 9 Depok. The research method used in this research is analytical method. The sampling technique used purposive sampling technique. Instruments for collecting data in this study were in the form of a learning style questionnaire and a test of critical thinking skills. All students of class X MIPA 1 were identified with the type of learning style by using learning styles and critical thinking skills tests taken by 6 students representing each type of learning style of 2 students. The test is carried out on the Absolute Value material. Furthermore, the analysis of all data is carried out with the following steps: data reduction stage, data presentation stage, and conclusions. The results showed that: 1) students with visual learning styles were able to overcome indicators at the stage of providing simple explanations and arranging tactics but were less able to meet indicators at the inference stage, 2) students with auditory learning styles were less able to reach the stage of providing simple explanations but were able to in arranging strategies-tactics and inference stages, 3) students with kinesthetic learning styles are able to fulfill all indicators at the stage of giving simple explanations, setting strategies-tactics, and inferences